Pengaruh Kepemimpinan Transformasional dan Employee Engagement terhadap Kinerja Karyawan PT Taspen (Persero) Kantor Cabang Utama Surabaya - Pramita Trisnaning Cahyandani (Jurnal Ilmu Manajemen, 2021)
This study aimed to examine and analyze transformational leadership and employee engagement on employee performance at PT. Taspen (Persero) Kantor Cabang Utama Surabaya. Quantitative methods use to process questionnaire that employees have filled in. The study population was all employees of PT. Taspen (Persero) Kantor Cabang Utama Surabaya consisting of 63 employees. The analytical tool used is multiple linear regression analysis by IBM SPSS 23 software. This study indicates that transformational leadership has a positive impact on employee performance. Employee engagement has a positive impact on employee performance. Transformational leadership and employee engagement can affect the performance of employees of PT. Taspen (Persero) Kantor Cabang Utama Surabaya.